Influence of precipitate-assisted nucleation on the microstructure and mechanical properties of Al-Mg-Si-Cu-Zn alloys. Issue 11 (3rd June 2019) - Li, G.J.; Guo, M.X.; Du, J.Q.; Zhang, J.S.; Zhuang, L.Z.; Lavernia, E.J.
ABSTRACT: The influence of precipitation on the recrystallization nucleation and mechanical properties of Al-Mg-Si-Cu-Zn alloys was investigated by means of tensile tests, SEM, TEM, XRD and EBSD. The results reveal that there are distinct contributions from the various precipitates that form during annealing and that these critically influence the evolution of microstructure and its associated texture, as well as mechanical behaviour. In contrast to alloy sheets A, B, and C annealed at a lower temperature or for a shorter time, the T4P alloy sheet D with an annealing at 450°C for 3 h not only possesses almost identical strength and elongation, but also a higher average r (0.659) and n (0.313) values, and also a lower Δ r (0.091) value. After solution treatment, the four alloy sheets are comprised of equiaxed grains with somewhat different grain sizes and different textures, but texture volume fraction and grain size in alloy sheet D both are decreased due to the effect of precipitate-assisted nucleation during solution treatment. The corresponding nucleation and growth mechanisms of recrystallization grains were established and the relationship between textures and r value in the four alloy sheets was also analyzed on the basis of a Visco-plastic self-consistent (VPSC) model.